2020
DOI: 10.1186/s13102-020-00189-6
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of low back pain among young basketball players with lower extremity pain: a cross-sectional study

Abstract: Background Low back pain (LBP) is a common problem among young basketball players in addition to lower extremity injuries. However, studies that focus on LBP with lower extremity pain are limited. From the perspective of the kinematic chain, disrupted lower extremity function can lead to LBP. The association between these two symptoms in basketball players, however, has not been reported. Therefore, this study aimed to clarify the association between lower extremity pain and LBP among young basketball players.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Previous systematic reviews have reported that the prevalence of LBP in these athletes ranges from 17% to 94% [1,2]. Specifically, the prevalence of LBP in past 12 months has been reported from 6.5% to 47% in soccer players [3][4][5] and from 12.8% to 44% in basketball players [6][7][8]. A previous episode of LBP is often predictive of future back injury [9], which will affect sports participation and performance [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews have reported that the prevalence of LBP in these athletes ranges from 17% to 94% [1,2]. Specifically, the prevalence of LBP in past 12 months has been reported from 6.5% to 47% in soccer players [3][4][5] and from 12.8% to 44% in basketball players [6][7][8]. A previous episode of LBP is often predictive of future back injury [9], which will affect sports participation and performance [9].…”
Section: Introductionmentioning
confidence: 99%
“…1 Pain is an important warning signal for the body that something is wrong, 5 and back pain is a common problem in athletes. [6][7][8][9] According to a study of 590 basketball athletes, 12.9% reported low back pain. 10 In many cases, pain can even prevent subjects from performing daily activities.…”
Section: Introductionmentioning
confidence: 99%
“…Of the included studies, 33 studies (reported in 42 papers)21 25 30 33 39 40 43–45 48–83 scored above 65% on the quality appraisal tool, indicating high quality (online supplemental table 4). Only 16 studies (reported in 20 papers) described reasons for non-response or compared the sample and target population,17 26 32 39 40 48 50 54 56–62 69 77 79 84 85 though this criterion was only applicable to 63 studies. Of the five studies that included interviews, one used a validated, reproducible or adequately described interview format 62.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 studies that included a clinical examination, 4 used a validated, reproducible or adequately described examination method,22 32 35 68 such as the use of a standardised pro forma for injury reporting. Only 38 studies had a precise anatomic location of back pain or reference to an easily attainable article that contained a precise location 25 27 31 33 44 45 49–56 58–64 66 67 69 71 73–79 81–83 86–88…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation